Evaluating e-learning satisfaction with a quali-quantitative analysis of the open-ended responses: a case study of a continuing medical education course - Lugli, Camilla; Mazzaccara, Alfonso; Guerrera, Debora; Arecchi, Serenella; D'Ancona, Fortunato; Fadda, Giulia; Giannitelli, Stefania; Filippini, Tommaso; Palandri, Lucia; Righi, Elena; Favazzi, Ughetta Maria (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: Continuing education is essential in the health sector, ensuring professionals stay updated with advancements and best practices. The growing reliance on e-learning, accelerated by the COVID-19 pandemic, has improved accessibility and engagement along with the use of interactive methodologies. These factors showed to increase participant satisfaction. The Italian National Institute of Health (ISS) has implemented e-learning courses using problem-based learning (PBL) to foster active learning. This study evaluates the informative potential of the feedback survey (FS) used in ISS courses, focusing on a quali-quantitative analysis of participant feedback from a case study course. Methods: The case study course was designed using PBL methodology and targeted healthcare professionals across all disciplines. Data on sociodemographic characteristics and FS responses to closed and open-ended questions were extracted from EDUISS, ISS e-learning platform. A combination of quantitative and quali-quantitative text analysis was conducted to examine responses and develop a thematic vocabulary. Results: A Satisfaction Training Index, derived from 18 Likert-scale items, showed high overall satisfaction (mean: 4.4, SD: 0.6) among 47,017 respondents out of 68,805 total participants (70% females, 57% nurses). Text analysis of open-ended responses revealed predominant themes of positive evaluations and clarity of content and delivery. Suggestions focused on enhancing content depth and improving evaluation methods. Thematic analysis produced a thematic vocabulary of 4 macro-themes and 13 specific themes covering positive comments (90%) and suggestions (>70%). Conclusions: Although overall satisfaction levels were high, the qualitative analysis of open-ended responses provided actionable insights for improving course delivery and tools.